The Use of Artificial Intelligence Combined with Wireless Network in Piano Music Teaching - Linna Yu (Wireless Communications and Mobile Computing, 2022)
Artificial intelligence (AI) development gives a new development direction to the traditional education model. The education reform in the intelligent environment is urgent. Under this background, the theory, methods, and characteristics of intelligent music education are expounded based on traditional piano music education. AI and Internet-based smart piano education is introduced. The characteristics of smart piano and its methods of assisting music teaching are analyzed. Moreover, literature review and questionnaire are adopted based on intelligent music education and smart piano theory. With two universities A and B in Nanjing as the research object, the questionnaire is designed to investigate and analyze the related problems of smart piano-assisted piano basic teaching in detail. The results show that smart piano positively improves skill training and psychological training in piano teaching. Piano major learners believe that smart piano can obviously help beginners and people with low piano levels. However, smart piano is not as good as traditional piano for high-level learners. In actual teaching, teachers should use different strategies for different levels of learners. Regarding curriculum quality, teachers have not fully played the role of the smart piano, and the curriculum of smart piano-assisted basic piano teaching still needs improvement. Finally, corresponding countermeasures and suggestions for the development direction of smart piano in piano music education are put forward according to the current situation of the smart piano. The results can reflect the current situation of smart piano-assisted basic piano teaching, provide a reference for researchers in related industries, and promote the related development of smart piano.